Factors Affecting Musyarak Financing In Sharia Banking In South Sulawesi - Husaini, Hambali; Aswiwin; Habiba (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2022)
The Islamic banking system is actually not limited to customers who have religious emotional ties (Muslim communities). Sharia banking services can be enjoyed by anyone regardless of their religion, as long as they are willing to follow the way of doing business that is permitted by sharia. society needs financial institutions that are strong, transparent, fair and committed to helping improve the economy and customers’ businesses. Musyarakah contract is one of the permissible contracts according to sharia based on the arguments in the Qur’an and Sunnah. So that the factors that influence musyarakah financing services are important to study.